Contrast With Compression Therapy Enhances Muscle Function Recovery and Attenuates Glycogen Disruption After Exercise. (March 2023) - Colantuono, Vincent M.; Oakley, Ryan; Hatfield, Disa L.; Penailillo, Luis; Lateef, Shabnam; Earp, Jacob E.
Background: Exercise-associated muscle damage (EAMD) temporally impairs muscle function and intramuscular glycogen storage. Contrast with compression (CwC) therapy provides localized EAMD treatment with minimal changes in core/tissue temperature that can impair glycogen resynthesis. Hypothesis: CwC will enhance the recovery of strength, power, and joint mobility, reduce markers of EAMD, and attenuate the disruption of glycogen storage observed after damaging exercise. Study Design: Randomized controlled trial with crossover design. Level of Evidence: Level 2. Methods: Ten men completed 2 bouts of eccentric elbow flexor exercise, separated by 1 week, using contralateral arms. After each bout, participants received either CwC therapy (at 0, 24, and 48 h postexercise) or no therapy with intervention order and limb randomly assigned. Prior to (pre-exercise) and 1, 24, 48, and 72 h after each exercise bout, muscular strength, muscular power, intramuscular glycogen, creatine kinase, muscle thickness, muscle soreness, pressure pain threshold, active elbow flexion, passive elbow extension, and dietary intake were assessed. Comparisons were made between conditions over time (interaction effects) using separate repeated-measures analyses of variance/multivariate analyses of variance and effect sizes (Cohen d ) to describe treatment effect at each time point. Results: Significant interaction effects were observed for muscular strength ( d = 0.67-1.12), muscular power ( d = 0.20-0.65), intramuscular glycogen ( d = 0.29-0.81), creatine kinase ( d = 0.01-0.96), muscle thickness ( d = 0.35-0.70), muscle soreness ( d = 0.18-0.85), and active elbow flexion ( d = 0.65-1.17) indicating a beneficial effect of CwC over time ( P ≤ 0.05). In contrast, no significant interaction effect was observed for pressure pain threshold or passive elbow extension ( P > 0.05). Conclusion: These results support the use of CwC for the recovery of muscle function after damaging exercise in male patients and indicate that CwC attenuates, but does not remove, the disruption of intramuscular glycogen stores observed after intense eccentric exercise. Clinical Relevance: Glycolysis-dependent athletes may benefit from CwC therapy after training/competition that causes EAMD.